Curriculum 2013, Physical Fitness, SMA Malemputra Aceh Besar - irwandi fauzi; Armaidi Armaidi (Sport Pedagogy Journal, 2023)
development and assessment of learning processes based on the 2013 Curriculum to improve the physical fitness of high school students. The 2013 curriculum emphasizes a competency-based learning approach that enables students to develop the knowledge, skills, and attitudes necessary to succeed in life. In terms of physical fitness, students need knowledge of the importance of maintaining physical health and fitness, as well as skills in performing effective physical activity. The first step in implementing the development and assessment of the learning process based on the 2013 Curriculum to improve the physical fitness of high school students is to adjust the curriculum to the needs of students. This is important because students have different needs in terms of physical activity and physical fitness. The curriculum should include sports and health-related competencies relevant to the student's needs.